The Effects of Entrepreneurship Education on Job Value, Entrepreneurial Self-Efficacy and Entrepreneurial Intention - et. al., KeSu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Along with the global financial crisis, China's economic downturn continues, resulting in an economic crisis and high unemployment rates. Under the condition that the current employment anxiety continues, the interest in start-ups by the unemployed, employees, and college students is increasing. Because the concept of lifelong workplace becomes somewhat blurred due to the increase in the average age, many people have become interested in start-up and education about start-up for relatively guaranteed economic activities.The purpose of this study is to verify whether the result of entrepreneurship education affects the entrepreneurship performance of university students. In addition, this study aims to structurally verify whether such education strengthens the entrepreneurial Intention in parallel with the occupational value and entrepreneurial self-efficacy. For this purpose, an online survey was conducted on 340 students who took entrepreneurship education or related classes among Chinese university students, and the structural relationship between entrepreneurship education, job value, self-efficacy and entrepreneurship will was empirically verified.The results of this study are summarized as follows. First, the entrepreneurship education for college students had a significant effect on the job value. Second, the start-up education for college students had a significant effect on the self-efficacy of start-up. Third, job value had a significant effect on entrepreneurial self-efficacy. Fourth, job value had a significant effect on entrepreneurial intention; finally, entrepreneurial self-efficacy had a significant effect on entrepreneurial intention.